The Role of Geomorphologic Factors in Economic Activities of Border Regions (Case Study: Sardasht County) - Javad Heshmati; Afshan Ghasemi; Rezvan Hemati (جغرافیا و پایداری محیط)
Geomorphologic factors are directly affected by the economic conditions of the areas and these factors can have a limiting and negative or positive effects. The effect of geomorphologic factors in the border regions is more important than the inner regions. Considering the importance of the issue, in this research, the impact of geomorphologic factors on the development or non-development of economic activities in Sardasht city has been evaluated. The research data include library information, digital information layers and the results of the questionnaire. In this research, firstly, the geomorphological situation of the area and its bottlenecks have been investigated. Then the situation of distribution of rural areas in slopes and heights has been investigated. Moreover, in order to investigate the role of geomorphologic factors in the development or non-development of economic activities of the city, 200 questionnaires have been used which are distributed in a chain method. Therefore, well-known people, including students and economic activists, have been used. The results indicate that about 70 percent of rural settlements are located in slopes with more than 20 percent and about 55 percent of rural settlements in elevations above 1400 meters. Therefore, the city faces many restrictions for the development of agricultural activities, infrastructure development, development of transport activities, as well as industrial development. Besides, the results of the questionnaires indicate that the geomorphologic situation dominating the region is considered as an effective factor in the lack of economic development, the growth of false occupations and smuggling of goods.